B lymphocyte-deficiency in mice promotes venous thrombosis. Issue 11 (November 2022) - Hasselwander, Solveig; Xia, Ning; Mimmler, Maximilian; Ascher, Stefanie; Knopp, Tanja; Reifenberg, Gisela; Karbach, Susanne; Ruf, Wolfram; Reinhardt, Christoph; Li, Huige
Abstract: Cells of the innate immune system, including monocytes and neutrophils, are key players in the process of venous thrombosis. T lymphocytes have recently been implicated in venous thrombus resolution but the role of B lymphocytes in thrombosis is unknown. The present study was conducted to address this question using a mouse model of partial ligation of the inferior vena cava. Although only a very low number of B cells was found in the venous thrombi of wild-type mice, B cell-deficient JHT mutant mice developed larger venous thrombi than the wild-type controls. Consistent with enhanced thrombogenesis, increased neutrophil counts were found in the circulating blood and in the thrombi of B cell-deficient mice. One of the mechanisms by which neutrophils contribute to venous thrombosis is the formation of neutrophil extracellular traps (NETs). In agreement, higher quantities of NETs were observed in the thrombi of B cell-deficient mice. In vitro assays showed no difference in the NET building capacity of the isolated neutrophils between B cell-deficient and wild-type mice, indicating that the enhanced NET formation in the thrombi of B cell-deficient mice is attributable to the increased number of circulating neutrophils in these animals. Furthermore, increased concentration of the clot-stabilizing macromolecule fibrinogen was detected in the plasma of B cell-deficient mice. In conclusion, B cell-deficiency in mice indirectly promotes venous thrombosis by increasing neutrophil numbers and elevating fibrinogen levels. Abstract : B lymphocytes; Neutrophils; Deep-vein thrombosis; Venous thromboembolism; JHT mouse.